Detection the Expression of IGF1 Gene and Evolution The Genotoxicity Using Some Genetic Test and Some Vital Variables in Breast Cancer Women - Al-Sammarraie, Hanan Waleed Muhamed (American Journal of Biology and Natural Sciences, 2025)
One key participant in carcinogenesis is the insulin-like growth factor 1 (IGF1) pathway. Previous research used prolonged administration of several IGF1 receptor agonists to animals. The second leading cause of cancer-related mortality among females is breast cancer, which also happens to be the most prevalent malignancy among women. Nearly 40% of all female cancers have this description. In order to evaluate genetic damage in a group of breast cancer patients, this research set out to investigate these assays and their applicability. Methods: All recorded cancer cases from March to October 2024. A total of 90 samples were obtained from females (ranging in age from 50 to 70 years) at the Oncology Center of the Saladin Health Department in Tikrit. Of these, 30 served as controls and 60 had breast cancer, a diagnosis that was confirmed by histopathological reports. The genotoxicity doses assessed in oral epithelial cells using the Micronucleus assay and Comet assay for DNA damage in peripheral lymphocytes demonstrated a significant rise in white blood cell concentration (8.30*±1.50) compared to the healthy control group (7.06±1.88). On the other hand, a decrease in PCV concentration (33.50*±1.13) compared to the healthy control group (36.40±3.16) and Hbg/DL(10.53±1.20) (9.86*±1.80) was observed (P≤0.05). Breast cancer patients had an average of 155.8 ± 4.75 mean micronuclei, which is greater than the healthy control group's 29.25 ± 4.37 average abnormalities in nuclei. The findings highlight an average rise in the number of impacted cells (*6.64± 1.2) and an average total number of cells (51.66 ± 18.19). There was a significant difference between the control group and the patients in terms of the average amount of damage (* 31.33 ± 12.15) and the IGF1 gene. These findings point to the possibility that micronucleus and comet estimates may be useful in estimating cellular genetic damage in breast cancer patients.